A component analysis of job interview training for young adults with autism spectrum disorder. (4th February 2019) - Rosales, Rocío; Whitlow, Helena
Abstract : The job interview is a vital component to acquire employment. Individuals with autism spectrum disorder may experience difficulties with job interviews due to notable deficits in social and communication skills. We evaluated the relative impact of several components of a job interview training package on six participants' responses to commonly asked interview questions. We used a multiple baseline design across participants to present the following components: written instructions, rehearsal and video self‐feedback with a commercially available training program, and verbal feedback delivered by the experimenter. Results demonstrated that all participants required an additional behavioral skills training session to meet our mastery criterion. However, once training was complete, all participants showed generalized performance when the interview questions were presented in a varied format and by a novel interviewer outside of the training environment. In addition, their performance was maintained at follow‐up.